2003
DOI: 10.4049/jimmunol.171.5.2694
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Effects of IFN-β in Multiple Sclerosis Patients

Abstract: The purpose of this report was to characterize the dynamics of the gene expression cascades induced by an IFN-β-1a treatment regimen in multiple sclerosis patients and to examine the molecular mechanisms potentially capable of causing heterogeneity in response to therapy. In this open-label pharmacodynamic study design, peripheral blood was obtained from eight relapsing-remitting multiple sclerosis patients just before and at 1, 2, 4, 8, 24, 48, 120, and 168 h after i.m. injection of 30 μg of IFN-β-1a. The tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
69
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 38 publications
3
69
0
Order By: Relevance
“…Not so surprisingly, several reports have demonstrated an induction of the type-I IFN response program in patients treated with IFN-b . 40,41 As anticipated, the one patient receiving IFN-b therapy clustered together with the RRMS high patients and showed an upregulation of IFN-induced genes. Although transcription-based prediction of IFN-b therapy has been studied, 42,43 future research in a large cohort of patients is needed to sort out whether the absence or presence of a type-I IFN response in the PB of patients with RRMS is a prognostic factor for successful treatment with IFN-b.…”
Section: Discussionmentioning
confidence: 84%
“…Not so surprisingly, several reports have demonstrated an induction of the type-I IFN response program in patients treated with IFN-b . 40,41 As anticipated, the one patient receiving IFN-b therapy clustered together with the RRMS high patients and showed an upregulation of IFN-induced genes. Although transcription-based prediction of IFN-b therapy has been studied, 42,43 future research in a large cohort of patients is needed to sort out whether the absence or presence of a type-I IFN response in the PB of patients with RRMS is a prognostic factor for successful treatment with IFN-b.…”
Section: Discussionmentioning
confidence: 84%
“…IFN-␤1a's reported mechanisms of action include inhibition of MHC class II expression on monocytes and microglia, suppression of T cell proliferation, regulation of IL-12/IL-10 cytokine transcription, and inhibition of inflammatory cell migration into the CNS via interference with VLA-4-mediated cell adhesion and matrix metalloproteinase 9 activity (3). However, IFN-␤'s effects are complex and cellular responses to IFN-␤ involve Ͼ500 genes (4), suggesting that some of the relevant mechanisms of action may still not be identified. Although IFN-␤ is secreted during the antiviral innate immune response, the physiological role of endogenous type I IFNs in the regulation of the adaptive immune response is poorly understood.…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%
“…Recently it was demonstrated that measuring the mRNA response of the IFNb-induced antiviral MxA protein ex vivo by quantitative PCR yields a good correlate of the bioavailability of IFNb in a given subject [16,20]. However, since there are inter-individually different response curves of the MxA mRNA expression, a small proportion of patients may be classified false-positively [21][22][23]. To minimize this potential error it would be ideal to compare individual MxA mRNA responses on IFNb therapy with the respective responses at treatment initiation of the same individual [24].…”
mentioning
confidence: 99%